(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Homemade guns are expanded throughout Thailand. Currently, the government does not fully inform the exact number of homemade guns, and there is no legitimate research of homemade guns. The objectives of this research were to explore situations and problems in controlling the possession and use and selling of homemade guns. It also explored some suggestions effective for the control measures for the possession and use and selling of homemade guns. This qualitative research collected data from document research and in-depth interviews from samples with a specific selection of 34 people. It has been found that the problem of homemade gun is from the provisions of the Firearms Act 1947, which is the only gun control law in Thailand. The aforesaid law requires homemade gun as criminalization and impose penalties for violators, which must be strictly on law enforcement by officials. It therefore becomes a limitation in the control of Thai homemade gun to exempt from the law such decriminalization for certain types of homemade guns, especially those used in rural areas for self-defense, agriculture, livestock, and hunting. In addition, the influence of internet technology and online social media created the market for homemade guns on computer systems as well as new users of homemade guns. However, officials under the Firearms, Ammunition, Explosives, Fireworks and Imitation of Firearms Act 1947 and police still do not have the power to end the situation on the said computer system. Therefore, the guidelines for controlling the possession and use and selling of homemade gun require formal social control mechanisms and reinforcements with informal social control by using positive social media and strengthening social norms regarding public safety.